2017
DOI: 10.1177/0017896917716204
|View full text |Cite
|
Sign up to set email alerts
|

Playwork in prison as a mechanism to support family health and well-being

Abstract: Objective: The health of the prison population has become an increasing concern, given the disproportionate rates of ill health in this population. Moreover, the challenges faced by prisoners' families and their children are also becoming more apparent, with prisoners' children being more likely than other children to experience mental and emotional health problems and more likely to go to prison themselves. Prison visits are an integral part of institutional structures and are a key way by which families stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The needs and experiences of families of those involved in the criminal justice system has gained increasing visibility in both academia and policy over the last decade (Booth, 2020;Condry & Minson, 2020;Hutton & Moran, 2019;Lockwood et al, 2021;Woodall & Kinsella, 2017). However, the focus of this work has been directed primarily toward the families of those in prison.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needs and experiences of families of those involved in the criminal justice system has gained increasing visibility in both academia and policy over the last decade (Booth, 2020;Condry & Minson, 2020;Hutton & Moran, 2019;Lockwood et al, 2021;Woodall & Kinsella, 2017). However, the focus of this work has been directed primarily toward the families of those in prison.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in England and Wales, increasing policy interest has been directed toward the importance of familial contact during custody and the role of children and families of prisoners in reducing reoffending (Farmer, 2017;HMIP, 2016); with the social capital that they can provide considered vital in supporting effective resettlement (Booth, 2020). The emergent body of academic work has also brought attention to the wide range of negative impacts on those with a family member in prison (Jones & Wainaina-Wozna, 2013;Lee et al, 2014;Lanskey et al, 2019;Long et al, 2019;McGinley & Jones, 2018); with a distinct body of work identifying the specific difficulties experienced by children with a parent in prison (Jones & Wainaina-Wozna, 2013;Phillips et al, 2002;Scottish Centre for Crime and Justice Research, 2019;Woodall & Kinsella, 2017). Despite this growing body of knowledge, significant gaps remain.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the needs of families of prisoners have historically been overlooked by policy makers in the UK (Booth, 2020;Perry, 2016;Woodall and Kinsella, 2017). More recently the Farmer Review (2017) explored the role of prisoners' families as a 'resettlement agency' and a pathway to reducing re-offending.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic broke at a time when the needs and experiences of families of those in prison were gaining more visibility in both academia and policy (Booth, 2020; Woodall and Kinsella, 2017). In England and Wales, the Farmer Review (2017) concluded that prisoners’ families were the ‘golden thread’ to effective resettlement.…”
Section: Introductionmentioning
confidence: 99%
“…Equally, the increased risk of COVID to those in prison has resulted in families experiencing extreme anxieties (Testa and Fahmy, 2021). With families of prisoners across the globe equally more likely to have complex health needs themselves (Lockwood et al, 2021; Raikes et al, 2019; Woodall and Kinsella, 2017), the distress experienced is likely compounded by concerns for their own health and well-being during the pandemic.…”
Section: Introductionmentioning
confidence: 99%